Carcass and meat quality of triple cross (Ghungroo x Hampshire x Duroc) fattener pigs - Thomas, R. (2023)
A triple cross pig variety (Ghungroo x Hampshire x Duroc, G25H25D50) was developed as a fattener pig. Pure parental lines of Hampshire and Duroc (male) and Ghungroo (female) pigs were used as exotic and indigenous germplasm, respectively. A total of 14 gilts and 20 barrows from triple cross pigs were slaughtered at the age of 10 months for evaluating the different parameters. Carcass traits indicated a meat: bone ratio of 2.95 and fat: lean ratio of 0.17 for this pig variety. The carcass length ranged from 61.5 cm – 93 cm, while that of the loin eye area varied from 1.30 in2 – 5.50 in2 . Back fat thickness at three-quarters of the length of the transverse section of the exposed M. longissimus thoracis et lumborum between the 10th and 11th ribs was in the range of 0.7 cm – 2.25 cm. Moisture: protein ratio varied from 3.20 to 3.39 and no significant (P>0.05) difference was observed between gilts and barrows. The cholesterol content in M. longissimus thoracis et lumborum varied from 47.83 mg/100g – 71.19 mg/100g, with an average of 59.70 mg/ 100g.